Genetic predisposition to immune dysregulation and extracellular matrix remodeling in cardiac arrhythmia reveals potential mediation by SPP1+ macrophages - Jie-Yuan Jin; Jie-Yuan Jin; Shuai Guo; Yao Deng; Ya-Qin Chen; Chen Liang; Yu-Jie Jiang; Wang Zhao; Rong Xiang (Frontiers in Cell and Developmental Biology)
IntroductionCardiac arrhythmia frequently co-presents with structural abnormalities such as cardiomyopathy and myocardial fibrosis, creating a bidirectional relationship where electrical disturbances and structural remodeling exacerbate each other. Current genetic studies focus on ion channel variants, which explain part of the etiology. Molecular mechanisms underlying arrhythmias pathogenesis and its progression warrant further investigation.MethodsWe performed whole-exome sequencing on 50 arrhythmia patients (21 females, 29 males), predominantly with early-onset disease (94% ≤ 35 years). We focused on exonic deleterious mutations that are rare in healthy populations. The identified recurrently mutated (r.m.) genes were analyzed using protein-protein interaction networks and gene ontology enrichment for functional modules. These genomic insights were integrated with single-cell data (7 arrhythmias, 5 controls) to examine cell-type-specific gene expression changes, with particular focus on SPP1+ macrophage states.ResultsWe identified 132 r.m. genes present in ≥30% of patients in our cohort, with significant functional module enrichment in immune regulation, tissue homeostasis, extracellular matrix, and vesicle transport pathways. Single-cell analysis of 37,675 cells revealed conserved transcriptional signatures across cell types, characterized by enhanced cytokine responses and pro-fibrogenic programs. We discovered genetic determinants potentially underlying SPP1+ macrophage activation in arrhythmic hearts—a known mediator implicated in both inflammatory processes and fibrotic remodeling. Age-specific associations included ADAMTS7 mutations in very early-onset cases (≤20years; OR = 9.71 [2.38–47.74], P-value <0.001), while gender-specific variants included SLC9B1 (P-value = 0.017) exclusively in females. Additionally, OTOA mutations were associated with both relatively late onset (>20years; OR = 0.17 [0.04–0.68], P-value = 0.009) and female predominance (OR = 3.41 [0.92–13.58], P-value = 0.045).ConclusionOur exploratory analysis reveals how genetic variants may predispose arrhythmia patients to inflammatory and fibrotic processes. These findings may help guide future research into the molecular mechanisms underlying arrhythmia progression to structural heart disease and identify candidate pathways for therapeutic investigation.